Effects of negative roll gap rolling and pulsed current annealing on microstructure and properties of Invar 36 alloy thin strip - Enzheng Wang; Liping Bian; Yao Zhao; Hongwei Ping; Tao Wang; Zhongkai Ren; Shuyong Jiang; Qingxue Huang (Journal of Materials Research and Technology)
This study proposes a novel processing route combining negative roll-gap cold rolling with pulsed current annealing for manufacturing high-performance Invar 36 alloy thin strips. The microstructure evolution and texture development were systematically investigated under various rolling reduction ratios and pulsed current annealing parameters. The results indicate a strong correlation between cold rolling reduction ratios and the pulsed current annealing process. Negative roll gap cold rolling leads to a significant increase in strength and a sharp decrease in ductility as the cold rolling reduction ratios rise. After 90 % cold rolling reduction, the processed specimen achieves enhanced mechanical properties with a tensile strength of 820 MPa and a hardness of 283 HV. This is attributed to the increased dislocation density, the formation of low-angle grain boundaries (LAGBs) and deformation twins, and the development of strong crystallographic textures including copper-type {112}<111>, brass-type {110}<112>, and S-type {123}<634>. Pulsed current annealing significantly enhances the ductility of rolled thin strips while concurrently reducing their strength. This improvement is attributed to dynamic recovery, recrystallization and the development of a strong cubic texture {100}<001>, driven by high-energy pulsed current induced thermal and non-thermal effects. High-strength-ductility Invar 36 alloys, including a 0.5 mm-thick thin strip with a tensile strength of 650 MPa, yield strength of 575 MPa, and fracture elongation of 5.9 %, as well as a 0.1 mm-thick ultra-thin strip with a tensile strength of 600 MPa, yield strength of 520 MPa, and fracture elongation of 5.8 %, were successfully fabricated using a combined approach of negative roll gap cold rolling with 50 % and 90 % reductions followed by pulsed current annealing for only 40 s. This approach provides a promising and efficient pathway for the rapid production of high-performance Invar 36 alloy thin strips.